2015
DOI: 10.1136/annrheumdis-2014-206504
|View full text |Cite
|
Sign up to set email alerts
|

The comparative effectiveness of oral versus subcutaneous methotrexate for the treatment of early rheumatoid arthritis

Abstract: ObjectiveTo determine the comparative effectiveness of oral versus subcutaneous methotrexate (MTX) as initial therapy for patients with early rheumatoid arthritis (ERA).MethodsPatients with ERA (symptoms ≤1 year) initiating MTX therapy were included from a multicentre, prospective cohort study. We compared the effectiveness between starting with oral versus subcutaneous MTX over the first year. Longitudinal multivariable models, adjusted for potential baseline and time-varying confounders, were used to compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
50
0
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(60 citation statements)
references
References 27 publications
4
50
0
6
Order By: Relevance
“…Interestingly, a claims database analysis of patients with RA initiating MTX found that although about one-half discontinued MTX at 1 year, more than one-third subsequently restarted MTX 52 . One study found patients who received MTX subcutaneously were less likely to add or switch to another nonbiologic DMARD or to add a biologic DMARD than patients treated with oral MTX 57 .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a claims database analysis of patients with RA initiating MTX found that although about one-half discontinued MTX at 1 year, more than one-third subsequently restarted MTX 52 . One study found patients who received MTX subcutaneously were less likely to add or switch to another nonbiologic DMARD or to add a biologic DMARD than patients treated with oral MTX 57 .…”
Section: Discussionmentioning
confidence: 99%
“…Hazlewood и соавт. [143] представили материалы мно-гоцентрового проспективного когортного исследования, включавшего 666 пациентов с ранним РА (длительность <6 мес), из которых 417 получали пероральную форму МТ, а 249 -подкожную. Пациенты, получавшие подкожную форму МТ, в среднем получали более высокую дозу препа-рата (22,3 мг/нед), чем принимавшие МТ перорально (17,2 мг/нед).…”
Section: подкожная форма метотрексатаunclassified
“…Hazlewood и соавт. [142] представили материалы мно-гоцентрового проспективного когортного исследования, включавшего 666 пациентов с ранним РА (длительность <6 мес), из которых 417 получали пероральную форму МТ, а 249 -подкожную. Пациенты, получавшие подкожную форму МТ, в среднем получали более высокую дозу препа-рата (22,3 мг/нед), чем принимавшие МТ перорально (17,2 мг/нед).…”
Section: подкожная форма метотрексатаunclassified